1998
DOI: 10.1111/j.1532-950x.1998.tb00160.x
|View full text |Cite
|
Sign up to set email alerts
|

Recovery From Sevoflurane Anesthesia in Horses: Comparison to Isoflurane and Effect of Postmedication With Xylazine

Abstract: Sevoflurane anesthesia in horses may contribute to a shorter, safer recovery from anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
90
1
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(105 citation statements)
references
References 8 publications
8
90
1
6
Order By: Relevance
“…The results of the study showed no statistically significant differences in cardiovascular or respiratory effects when comparing sevoflurane to isoflurane, which are consistent with previous reports in dogs, sheep, goats, humans and horses (Aida et al, 1996;Ebert et al, 1995;Hikasa et al, 1998;Matthews et al, 1998;Mutoh et al, 1997). Attempts to stand and recovery times appeared to occur faster for sevoflurane upon review of the data, although not statistically significant.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…The results of the study showed no statistically significant differences in cardiovascular or respiratory effects when comparing sevoflurane to isoflurane, which are consistent with previous reports in dogs, sheep, goats, humans and horses (Aida et al, 1996;Ebert et al, 1995;Hikasa et al, 1998;Matthews et al, 1998;Mutoh et al, 1997). Attempts to stand and recovery times appeared to occur faster for sevoflurane upon review of the data, although not statistically significant.…”
Section: Resultssupporting
confidence: 82%
“…Recovery quality of sevoflurane has been reported as comparable to or better than isoflurane in dogs and horses (Johnson et al, 1998;Matthews et al, 1998). Although this study found no statistical difference in the time to first movement, time to extubation, time to standing or attempts to stand between the two anesthetics, sevoflurane anesthetized calves appeared to awaken from anesthesia faster as indicated by the less time to first movement and extubation.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…However, adverse effects or toxicosis may appear if higher doses of fentanyl are administered. In any case, if the horses in Group SF were assisted and appropriate agents were administered, the qualities of the recoveries would be improved and become similar to those previously described for horses recovering from sevoflurane anesthesia [9,13].…”
Section: Discussionmentioning
confidence: 84%
“…In several studies agitation has been reported in people after anesthesia (29,30); however, Matthews et al (31) reported no complications in various animal species such as horse. Likewise, we did not find such complications in Angora goats.…”
Section: Discussionmentioning
confidence: 99%